Salivary and Serum B-cell Activating Factor (BAFF) Levels after Hydroxychloroquine Treatment in Primary Sjogren's Syndrome - MUMCU, GONCA; CİMİLLİ, ZÜHRE HALE (QUINTESSENCE PUBLISHING CO INC, 2013)
Purpose: Some evidence implicates a role of hydroxychloroquine (HQ) in the management of Sjogren's syndrome. This study evaluated the effect of HQ on saliva B-cell activating factor (BAFF) levels as well as health related quality of life (QoL) in patients with primary Sjogren's syndrome (pSS). Materials and Methods: Ten pSS patients who had been treated with HQ for at least 2 years and 15 healthy controls (HC) were included in the study. First, HQ was withdrawn for 12 weeks, then baseline evaluation was performed. Subsequently, HQ was restarted and further evaluations were carried out after 12 and 24 weeks of HQ treatment. Oral infection foci were eliminated by dental and periodontal treatments in both groups before enrollment. BAFF levels were evaluated with ELISA in serum and unstimulated mixed saliva. Salivary flow rates of patients and the control group were measured as well. Oral health quality of life (QoL) was evaluated by an oral health impact profile-14 (OHIP-14) questionnaire. Results: Salivary BAFF levels (median: 12.39 ng/ml) were significantly decreased by using HQ both at 12 (2.78 ng/ml, P = 0.008) and 24 weeks (0.54 ng/ml, P = 0.011). Similarly, decreases in serum BAFF levels (5.23 ng/ml) were seen at 12 and 24 weeks after HQ treatment (2.18 ng/ml, P = 0.008 and 0.0 ng/ml, P = 0.012, respectively). Serum and salivary BAFF levels were significantly lower in healthy controls (0.37 ng/ml and 0.0 ng/ml, resp.) compared to those of pSS before HQ therapy (P = 0.006 and P = 0.001, resp.). Unstimulated salivary flows were similar in patients treated with HQ after 12 (0.38 ml/min) and 24 weeks (0.50 ml/min) (P = 0.51) but higher than the patients' rate at baseline (0.04 ml/min) (P = 0.008). Conclusion: Salivary and serum BAFF levels were lowered in patients with pSS when treated with HQ. In addition, decreased disease activity and increased salivary flows can be achieved with HQ in pSS patients.
Keywords: BAFF level; hydroxychloroquine; Sjogren's syndrome; QUALITY-OF-LIFE; DISEASE-ACTIVITY; FAMILY BAFF; LYMPHOCYTES; EXPRESSION; VALIDITY; GLANDS; BLOOD